Antagonistic and ambivalent: The emotional politics of diversity management policy in a professional services firm. (August 2019) - Lee, Sandy
Abstract: In this paper I explore the complex emotions arising from the enactment of an institutional diversity policy and consider the political implications. Neoliberal policies and practices of diversity management have frequently been critiqued for their overly optimistic, depoliticized portrayals of diversity which conceal ongoing injustices. Drawing on research in the Melbourne branch of a multinational professional services firm, however, I highlight how both antagonism and ambivalence are evoked in the implementation of the firm's diversity policy. While managerial discourses normalise different emotional responses to gender and cultural diversity, unanticipated emotions also arise as workers negotiate their multiple identities. These emotions variously activate and placate resistance towards existing inequities and injustices. I therefore argue that both 'bottom up' emotions and those managed through 'top down' policy have the potential to motivate social change as well as hinder it. The paper extends existing debates in the emotional geographies of policy by challenging the common dichotomy made between the political possibilities of bottom up activism and top down management. By recognising the nuanced affective politics of different diversities learnings can be gleaned from the more successful aspects of diversity to develop policy initiatives able to achieve justice and equality for all disadvantaged groups. Highlights: Diversity policies normalise different emotions for gender and culture respectively. Certain emotions stirred by policy initiatives have potential in addressing injustices. Anger and frustration evoked for gender diversity mobilize progressive action. Cultural diversity discourses pacify efforts to challenge the status quo. Normative emotional responses to diversity are also resisted through workers' agency.